Experimental investigation on characteristics of venturi cavitating flow and Rhodamine B degradation in methanol solution. (June 2022) - Zhang, Jiahui; Luo, Jingquan; Wang, Yiwei; Dong, Bo; Xu, Zhen; Wang, Lin; Liu, Aixian; Guo, Xuqiang
Abstract: Hydrodynamic cavitation (HC) commonly occurs within industrial pipelines and its unsteady flow characteristics are of great significance for energy conservation and efficiency improvement. This study investigates the effects of methanol concentration (0–20 wt%) on the cavitating flow characteristics and the degradation of Rhodamine B (RhB) under operating conditions of a 0.7 MPa pressure drop, temperature of 30 °C, 200 passes through a venturi reactor, and an initial RhB concentration of 40 μmol/L. The transient cavitation behavior was monitored using a high-speed camera. The cavitation images show that the presence of methanol generates more stable bubbles, which results in less violent bubble collapse. The pressure pulsation and vibration induced by cavitation flow were synchronously measured using high-frequency pressure and acceleration sensors. The spectral analyses of the pressure pulsation indicate that methanol has no effect on the dominant frequency (∼5.5 Hz) at different positions, and the amplitude initially increases with increasing methanol concentration and then stabilizes. The pressure pulsation intensity increases due to the increased vapor pressure of the solution. The vibration spectral analyses show that methanol has little effect on the peak frequencies, which occur near 4.0 kHz and 14.3 kHz of the low and high-frequency bands, respectively, whereas the peak amplitude decreases with increasing methanol concentration. The per-pass degradation model of RhB in methanol solution considering pyrolysis of methanol was verified for the first time and show to adequately describe the experimental data. The degradation percentage and per-pass degradation factor decrease with increasing methanol concentration. The reduced surface tension of the solution prolongs the bubble lifespan and prevents bubble coalescence, thus weakening the vibration and degradation performance. The results provide important insight for cavitation applications and degradation modeling of mixed solutions. Graphical abstract: Image 1 Highlights: High concentration of methanol significantly influences cavitation dynamics. Methanol has opposite effects on amplitudes of pressure pulsation and vibration. Degradation of RhB in methanol solution can be explained by per-pass degradation model. Change in surface tension of methanol solution influences cavitation the most.